Enhancement of Drug Seeking Following Drug Taking in a Sexual Context Requires Anterior Cingulate Cortex Activity in Male Rats - Kuiper, Lindsey B.; Lucas, Kathryn A.; Mai, Vy; Coolen, Lique M. (Frontiers in Behavioral Neuroscience, 2020)
Individual variance in vulnerability to develop addictions is influenced by social factors. Specifically, drug-taking in a sexual context appears to enhance further drug-seeking behavior in human users, as these users identify the effects of drugs to enhance sexual pleasure as a primary reason for continued drug use. Methamphetamine (Meth) is commonly used in this context. Similarly, male rats that self-administered Meth immediately followed by sexual behavior display enhanced drug-seeking behavior, including attenuation of extinction and increased reinstatement to seeking of Meth-associated cues. Hence, drug-taking in a sexual context enhances vulnerability for addiction. However, the neural mechanisms by which this occurs are unknown. Here the hypothesis was tested that medial prefrontal cortex is essential for this effect of Meth and sex when experienced concurrently. First it was shown that CaMKII neurons in the anterior cingulate area (ACA) were co-activated by both Meth and sex. Next, chemogenetic inactivation of ACA CaMKII cells using AAV5-CaMKIIa-hM4Di-mCherry was shown not to affect Meth-induced locomotor activity or sexual behavior. Subsequently, chemogenetic inactivation of ACA CaMKII neurons during Meth self-administration followed by sexual behavior was shown to prevent the effects of Meth and sex on enhanced reinstatement of Meth-seeking but did not affect enhanced drug-seeking during extinction tests. These results indicate that ACA CaMKII cell activation during exposure to Meth in a sexual context plays an essential role in the subsequent enhancement of drug-seeking during reinstatement tests.